The Role of the Academic Library in the Accreditation of Universities in Ghana: A Case Study - Osei Kuffour Adjei, Kwabena; Osei-Bonsu, Moses (Ghana Library Journal, 2012)
The paper evaluates the libraries of three private university colleges in the Greater Accra Region of Ghana, namely the Central University College (CUC), Methodist University College (MUCG) and Wisconsin International University College (WIUC), which have gone through several accreditation processes as a case study. They were evaluated in terms of infrastructure, book stock, jinancial resources, staff, organisation and the use of facilities using the standards of the National Accreditation Board. The paper also examined the role of the libraries on the granting of accreditation, and the extent to which the accreditation process has improved service delivery in these libraries. The study employed the survey methodology and personal interviews in gathering information from a population sample of 201. The findings show that the National Accreditation Board (NAB) does not have any standard for initial library collections, but it stipulates that the Head of the Library must possess a Masters degree, and the library should be established a year before the university starts operation. The study showed that although the libraries faced several challenges they benefitted from the accreditation process through the provision of funds, recruitment of staff and enhanced service delivery which impacted on the parent institutions being granted accreditation. It concluded that there is a positive correlation between the provision of good library facilities in academic institutions seeking accreditation and the granting of accreditation by the National Accreditation Board.